Terapia regenerativa de la retinopatía diabética basada en células madre: revisión bibliográfica - Quilcat Sicche, Oscar Anderson (2022)
Type 2 diabetes mellitus appears when the body does not use insulin correctly, causing hyperglycemia, with the consequent compromise of organs and systems. Diabetic retinopathy is the most common microvascular complication of DM2 and is characterized as a progressive microangiopathy that selectively damages retinal arterioles, capillaries and precapillary venules6, Objective: To determine the efficacy of stem cells in regenerative therapy of retinopathy diabetic. Methods: literature review of studies published in Pubmed databases on regenerative treatment of diabetic retinopathy based on stem cells. Results: ASC stem cell-derived pericytes can integrate into retinal vessels, adopting pericyte morphology and marker expression, triggering an effective cytoprotective microenvironment in the retina. MSCs can improve histological structures affected by diabetic retinopathy by decreasing inflammatory activity, inhibiting apoptosis, and improving cell survival. Embryonic stem cells provide competent turnover of light receptors comparable to photoreceptors in normal retinas. Hematopoietic stem cell transplantation improves visual dysfunction and retinal neurodegeneration. Endothelial progenitor cells contribute to retinal neovascularization. Conclusion: regenerative treatment of diabetic retinopathy based on stem cells have different mechanisms of action, significantly improving visual function, reducing the damage caused by oxidative stress and apoptosis, promoting retinal neovascularization